A comprehensive review of canine parvovirus infection - Solikhah, Tridiganita Intan; Khairullah, Aswin Rafif; Gufron, Muhammad; Aulia, Revalin Zahra; Akram, Muhammad (Journal of Advanced Veterinary Research, 2026)
Canine Parvovirus 2 (CPV-2) remains one of the most significant and lethal infectious diseases of domestic dogs worldwide, decades after its pandemic emergence in the late 1970s. This comprehensive review synthesizes the current, multifaceted understanding of the virus. We explore its etiology as a non-enveloped, single-stranded DNA virus, its origin from Feline Panleukopenia Virus, and its rapid evolution into globally distributed antigenic variants (CPV-2a, 2b, 2c). The pathogenesis is detailed, highlighting a fecal-oral transmission route and a profound tropism for rapidly dividing cells, which dictates the classic clinical presentation of severe hemorrhagic gastroenteritis and profound leukopenia. This review critically examines the cornerstones of treatment, which remains aggressive supportive care centered on fluid resuscitation, broad-spectrum antibiotics to combat secondary sepsis, and antiemetic therapy. The critical role of vaccination with modified-live virus (MLV) vaccines is emphasized as the primary tool for prevention. We also address the central challenge in immunization: navigating the "window of susceptibility" created by maternally derived antibody (MDA) interference, which persists as the primary cause of vaccine failure in puppies. Furthermore, this review addresses the formidable challenges of control, driven by the virus’s exceptional environmental resilience, which necessitates specific disinfection protocols and strict biosecurity. Finally, the significant economic impact and public health importance are discussed, underscoring the disease’s substantial (though indirect) societal burden through high treatment costs, the psychological distress of "economic euthanasia," and its status as a paradigm for emerging infectious diseases